PENGAPLIKASIAN DIGITAL LIBRARY BERBASIS QR CODE UNTUK MENINGKATKAN KEMAMPUAN LITERASI MEMBACA SISWA SEKOLAH DASAR - Syadila Irvi Aprisha; Dian Permata Sari Kusuma Dayu; Rosniwaty; Himatul Khoiroh; Andi Buniyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve the reading literacy skills of elementary school students.The subjects of this study were fifth grade students at SDN Gading V Surabaya,a number of students 13 males and 18 females. The method used was the classroom action research method through 2 learning cycles.Each cycle carried out planning, implementation, observation and reflection activities. The results of the first cycle of research produced 63% success in learning outcomes, while the results of the second cycle produced 78% success in learning outcomes, which in these two cycles there was an increase of 15% from the previous cycle.